Final disposal and environmental impact of photovoltaic cells (Publicaciones en Ciencias y Tecnología, 2021)
The purpose of this work is to describe the process of final disposal of photovoltaic cells. It shows an overview of the cells, their industry and types. Additionally, the manufacturing materials and the final disposal process are described, describing their advantages and disadvantages. This process is classified according to the separation of materials, the type of cells, and their impact on the environment.
Keywords: photovoltaic panels; final disposal; photovoltaic cells; impact on the environment